Adiponectin is functionally active in human islets but does not affect insulin secretory function or beta-cell lipoapoptosis. - Staiger, K; Stefan, N; Staiger, H; Brendel, MD; Brandhorst, D; Bretzel, R; Machicao, F; Kellerer, M; Stumvoll, M; Fritsche, A; Häring, H (2005)
CONTEXT: The adipokine adiponectin has insulin-sensitizing, antiatherogenic, and antiinflammatory properties. Mouse and human adiponectin receptor-1 and -2 have been cloned, both of which are expressed in various tissues and mediate effects of globular and full-length adiponectin. Whether adiponectin affects insulin secretion and beta-cell apoptosis and whether plasma adiponectin is associated with beta-cell function in humans is under investigation. DESIGN AND METHODS: In human islets from multiorgan donors, we investigated expression of adiponectin receptor-1 and -2. Furthermore, glucose-stimulated insulin secretion was determined by RIA. In addition, we investigated fatty acid-induced beta-cell apoptosis by terminal dUTP nick end labeling and flow-cytometric cell cycle analysis (sub-G1 formation). In humans in vivo, insulin secretory function was measured during hyperglycemic clamps in 65 normal glucose-tolerant subjects. We determined first and second phase of glucose-stimulated, glucagon-like peptide-1-stimulated, and arginine-stimulated insulin secretion. RESULTS: Adiponectin receptor-1 and -2 are expressed in human islets at the mRNA and protein level. Moreover, full-length adiponectin induces phosphorylation of acetyl coenzyme A carboxylase. However, adiponectin did not affect basal or glucose-stimulated insulin secretion or basal or fatty acid-induced beta-cell apoptosis. In vivo, fasting plasma adiponectin concentrations were not associated with glucose-stimulated first- and second-phase insulin secretion or with glucagon-like peptide-1- or arginine-stimulated insulin secretion (all P > 0.42). CONCLUSIONS: These data support a regulatory role of adiponectin in human islets; however, adiponectin does not seem to affect insulin secretion or basal/fatty acid-induced beta-cell apoptosis in humans.